2013
DOI: 10.1002/hed.23226
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic total laryngectomy: Report of 3 cases

Abstract: We present 3 cases of transoral robotic surgery (TORS)-assisted TL in patients requiring narrow field laryngectomy without requirement for neck dissection. In reviewing these cases we provide a discussion of pertinent preoperative and intraoperative considerations that can assist in facilitating successful completion of the procedure. In particular, appropriate assessment at the pinsertlinePOLA_Del_Blank_PgPOLA_Shift_FramePORT_rem_fpg_underremovelinetabminilanning endoscopy in addition to a methodical surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 12 publications
0
66
0
1
Order By: Relevance
“…Dowthwaite et al [11] reported a case series in which TORS-TL was attempted in 3 patients, but with 1 of these cases requiring to be abandoned due to poor laryngeal visualisation. The cases included 1 low-grade subglottic chondrosarcoma, 1 non-functioning larynx due to chondronecrosis following prior treatment with external beam radiotherapy for metastatic cervical SCC of unknown primary origin, and 1 idiopathic bilateral vocal cord paralysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dowthwaite et al [11] reported a case series in which TORS-TL was attempted in 3 patients, but with 1 of these cases requiring to be abandoned due to poor laryngeal visualisation. The cases included 1 low-grade subglottic chondrosarcoma, 1 non-functioning larynx due to chondronecrosis following prior treatment with external beam radiotherapy for metastatic cervical SCC of unknown primary origin, and 1 idiopathic bilateral vocal cord paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…TORS total laryngectomy (TORS-TL) has previously been described [9,10,11,12], and has been met with scepticism as to its ultimate clinical benefit. This is because the overwhelming majority of patients requiring total laryngectomy have laryngeal SCC as the indication for surgery and this usually requires a concomitant bilateral neck dissection, largely obviating the usefulness of a minimally invasive approach to the primary site.…”
Section: Introductionmentioning
confidence: 99%
“…After description of the surgical technique by Lawson et al [73], 2 more case series have been published on robotic total laryngectomy [74], [75]. Robotic total laryngectomy seems to have two main advantages.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
“…However, in their articles, the authors also describe that in 1 of 3 [74] and 2 of 7 [75] cases, respectively, conversion to open technique had to be performed. In addition, Smith et al describe the occurrence of pharyngocutaneous fistulas in 2 of 7 cases, while the patient population consisted of patients with recurrent tumor disease and 6 patients underwent salvage surgery.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
See 1 more Smart Citation